2008
DOI: 10.1111/j.1532-950x.2008.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Model for Testing Novel Implants for Equine Laryngoplasty

Abstract: This model will allow testing of multiple novel techniques and may facilitate development of improved techniques for prosthetic laryngoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 24 publications
(59 reference statements)
5
41
1
Order By: Relevance
“…Perilaryngeal adhesions and fibrosis of the cricoarytenoid joint occur to varying degrees after LP and surgical arthrodesis of the cricoarytenoid joint is performed by some surgeons, which may prevent loss of ACA. Adhesion formation may explain why most abductory loss we observed occurred in the first 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Perilaryngeal adhesions and fibrosis of the cricoarytenoid joint occur to varying degrees after LP and surgical arthrodesis of the cricoarytenoid joint is performed by some surgeons, which may prevent loss of ACA. Adhesion formation may explain why most abductory loss we observed occurred in the first 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…These include stainless steel wire, cables, washers, nylon, polyethylene, and braided polyester . Braided polyester is currently the most commonly used material for equine laryngoplasty . A recent in vitro study compared 3 materials and identified the braided polyester, Ethibond™ (5 USP or 7 metric, Ethibond Excel™, Ethicon, Inc., Somerville, NJ) to be the most appropriate material for laryngoplasty; however, none of the materials were elastic (2 Ethilon® and 5 Fiberwire®) …”
mentioning
confidence: 99%
“…This could be overcome with incorporation of stepwise cyclic loading suggested by Willsallen et al in an attempt to incorporate the benefits of applying cyclic load and reach failure points obtained during single load to failure. Alternatively, ex vivo inspiratory pressure models could be used for evaluation of alternative materials for prosthetic laryngoplasty …”
Section: Discussionmentioning
confidence: 99%